Redesign of workstations to minimize musculoskeletal disorders for guitar workers in Indonesia - Pratiwi, Indah; Jannah, Isnainiyah Wardatul (OPSI, 2024)
This study aims to determine and analyze body parts that experience musculoskeletal disorders (MSDs) and muscles that experience fatigue in guitar-making workers. The method used is the Nordic Body Map (NBM) to determine MSDs complaints, including complaints of pain in 28 parts of the worker's body, and the Muscle Fatigue Analysis (MFA) method to determine muscle fatigue that occurs in each part of the body by determining the level of effort, duration of work, and frequency of work movements. The results of research using NBM were 2 workers with high risk, 3 workers with medium risk, and 7 workers with low risk. The results of the MFA method were that 3 workers experienced muscle fatigue in the very high category with priority in the neck, back, shoulders, right arm, wrist and feet. Efforts to minimize the risk of MSDs by redesigning work facilities using SolidWorks software and reducing the risk of muscle fatigue by improving work facilities, improving the layout of the production floor, and encouraging workers to stretch their muscles and exercise regularly.